2006
DOI: 10.1177/1934578x0600101005
|View full text |Cite
|
Sign up to set email alerts
|

Progress on Cassaine-Type Diterpenoid Ester Amines and Amides (Erythrophleum Alkaloids)

Abstract: The structures, spectral characteristics, and bioactivities of 39 natural cassaine-type diterpenoid ester amines and amides (Erythrophleum alkaloids) and 31 synthetic analogues are reviewed. Cassaine-type diterpenoid ester amines and amides, the so called Erythrophleum alkaloids, have the skeleton of cassane-type diterpenoids with a N-containing side chain, and are classified into two groups, ester amines and amides. Cassaine-type diterpenoid ester amines and amides show remarkable inotropic action on the hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Thus, compound 8 is β-D-glucopyranosyl 6α-hydroxy-cassamate. Selected compounds (3)(4)(5)(6)(7)(8) were evaluated for their cytotoxicity against HCT-8, Bel-7402, BGC-823, A549, and A2780 cell lines. As determined by a MTT assay, the active substances were compounds 5-7, which had an ethoxy attached to C-16 and showed moderate cytotoxic activity against these cell lines (l " Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, compound 8 is β-D-glucopyranosyl 6α-hydroxy-cassamate. Selected compounds (3)(4)(5)(6)(7)(8) were evaluated for their cytotoxicity against HCT-8, Bel-7402, BGC-823, A549, and A2780 cell lines. As determined by a MTT assay, the active substances were compounds 5-7, which had an ethoxy attached to C-16 and showed moderate cytotoxic activity against these cell lines (l " Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…It is known by the name ''Gemu'' and used by native Chinese as invigoration and promoting blood circulation agents (Cui and Ran, 1993). Previously, various components including alkaloids (cassaine diterpenoid amines and amides) (Culvenor et al, 1971;Cronlund, 1973;Qu et al, 2006b) and terpenoids (Li et al, 2004;Yu et al, 2005;Tsao et al, 2008) were reported from the genus Erythrophleum. The alkaloids showed a digitalis-like action on the heart (Cronlund and Sandberg, 1976;Verotta et al, 1995) and cytotoxic activity against some tumor cell lines (Loder et al, 1974;Loder and Nearn, 1975;Qu et al, 2006a).…”
Section: Introductionmentioning
confidence: 97%
“…The basic cassane type skeleton consists of a tricyclic diterpene with 20 carbon atoms, where the carbon in position C-13 is substituted by an ethyl group and the carbon in C-14 is substituted by a methyl group ( Figure 1 A). Various biosynthetic pathways have been proposed [ 23 , 24 , 25 ], in which cassane-type diterpenes are thought to be derived from biosynthetic rearrangements of the pimarane precursor Δ 8 ,15,-pimaradiene, itself originating from the cyclization of Δ 8 ,15,-labdadienyl pyrophosphate (LDPP) obtained from geranylgeranyl pyrophosphate (GGPP) in the terpenoid biosynthetic pathway (mevalonate pathway) ( Figure 1 A). The cassane-type backbone would derive from pimarane following migration of the methyl group carried by the carbon in position C-13 to the carbon in position C-14.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, a large number of different molecules have been described, differing in their substitution patterns at the level of the tricyclic skeleton and of the chain at the C-13 position. Cassaine-type diterpenoids fall into two groups: cassaine-type ester amine diterpenoids ( Figure 1 B) and cassaine-type amide diterpenoids ( Figure 1 C) [ 25 , 26 ] with the following particularities: Cassaine-type diterpenoids with an ester amine arm ( Figure 1 B) result from esterification between the carboxylic group of a cassane-type tricyclic diterpene acid and the alcohol group of an aminoethanol (often N -methylethanolamine (CH 3 -NH-CH 2 -CH 2 -OH) or N,N -dimethylethanolamine ((CH 3 ) 2 N-CH 2 -CH 2 -OH)) [ 26 ]. Ethanolamine can be formed by decarboxylation of a serine or by a transamination reaction (exchange of an amine group) between a glycoaldehyde and a glutamic acid [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation